(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
The basic intention of presented paper is to represent attend for approaching and clearing of debate about energy security in the frames of evolutionary NATO. The circumstances in the field of energy supplied doesn’t represent only economic thematic and they more occupied working agendas of the other international institution. More precisely, the paper is focusing on the approach politization and securitization of energy supply, the involvement and NATO role in the field of energy security as well as difficulty in definite of Alliance role. The paper is analyzed arguments which are needed for more serious NATO involvement and elaborate the beginnings of such thoughts in the Alliance strategic documents. As well as, the paper are analyzed elements which may be presents obstacle in clear definition of place and role of NATO in energy security. Energy security dilemma represents serious indicator of possible directions of Alliance evolution and its future contribution in contemporary international relations.